(untitled) (Research, Society and Development, 2024)
Manganese (Mn) is a first transition series metal considered highly relevant in several areas, from materials chemistry and metallurgy, through catalysis and even various sectors of bioionorganic chemistry. Manganese (Mn) presents a peculiar and extremely versatile redox behavior, it can be found in a range of different oxidation states. The control of possible oxidation states, aiming to obtain a series of applications, has been an issue to be controlled by everyone who works with the chemistry of this metal, since the physical-chemical properties of the different oxidation states can vary substantially. The present work aims to present fundamental aspects of the chemistry of the metallic element manganese (Mn), highlighting its redox variability as well as introductory topics to its coordination chemistry, covering organometallic compounds, and its relevant role in a biological environment. Therefore, this work shows an introduction to the chemistry of manganese, with special emphasis on its redox versatility and its behavior as a coordination center in metallic complexes, covering both the so-called organometallic chemistry and the biological implications of its coordination compounds. Furthermore, a comparative study is carried out with other metals, especially those from the first transition series.